The liver metabolic features of Mogroside V compared to Siraitia grosvenorii fruit extract in allergic pneumonia mice. (May 2022) - Liu, Yisa; Wang, Juan; Dou, Tong; Zhou, Luwei; Guan, Xiao; Liu, Guoxiang; Li, Xiaojuan; Han, Mengjie; Chen, Xu
Abstract: Background: For a long time, Siraitia grosvenorii fruit extract (SGFE) and its dominant compounds, mogroside V(MV) were both reported to have therapeutic effects on allergic pneumonia, while previous studies only stay on phenotype and mechanism of the two active ingredients, hardly have any studies compared the two ingredients on the effect of liver metabolic, and revealed the relationship between mechanism and liver metabolism. Objective: Here we elucidated and compared the curative mechanisms of SGFE and MV on allergic pneumonia through liver metabolomics. Methods: We established allergic pneumonia mice using ovalbumin, then treated the mice with SGFE, MV and positive drug of Suhuang Zhike Jiaonang. The effects of the drugs were evaluated by detecting inflammatory cytokines, pathological examination and liver oxidative stress biomarkers. We explored the metabolic features between SGFE and MV through liver metabolomics consequently. Results: At phenotype, we confirmed that MV and SGFE both inhibited the expression of inflammatory cytokines including interleukins-5 (IL-5), IL-13, IL-17 and OVA-induced immunoglobulin E, which can also relieve inflammatory cells infiltration and mesenchymal thickening in lung tissue compared with positive drug. In addition, both of them can alleviate oxidative stress damage in liver, while MV showed a superior effect than SGFE. In metabolomic analysis, the two ingredients were found to ameliorate inflammatory and oxidative reaction mainly in controlling pathways of Riboflavin metabolism and Glutathione metabolism. While SGFE were found to control other metabolic pathways such as Phenylalanine metabolism, Sphingolipid metabolism, Glycerollipid metabolism, Glycine, serine and threonine metabolism and Arginine and proline metabolism. Conclusion: From the results we can infer that the minor ingredients except MV in SGFE contribute poor function to the treatment of allergic pneumonia and MV may be the main functional constituent that relieve allergic pneumonia in SGFE. This study will be beneficial to figuring out a systematic theory of Siraitia grosvenorii active ingredients and proposing a guidance for pharmacology development. Graphical Abstract: ga1 Highlights: Exploring the curative mechanism of SGFE and mogroside V on allergic pneumonia on the metabolic level. Comparing the metabolic features between Siraitia grosvenorii fruit extract and mogroside V. The common metabolic pathway of Siraitia grosvenorii in liver is Riboflavin metabolism. Building up the metabolic network of the two active ingredients.